2011
DOI: 10.1074/jbc.m111.225375
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Base Excision Repair in Mediating Cisplatin Cytotoxicity

Abstract: Using isogenic mouse embryonic fibroblasts and human cancer cell lines, we show that cells defective in base excision repair (BER) display a cisplatin-specific resistant phenotype. This was accompanied by enhanced repair of cisplatin interstrand crosslinks (ICLs) and ICL-induced DNA double strand breaks, but not intrastrand adducts. Cisplatin induces abasic sites with a reduced accumulation in uracil DNA glycosylase (UNG) null cells. We show that cytosines that flank the cisplatin ICLs undergo preferential oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
121
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(137 citation statements)
references
References 47 publications
13
121
1
1
Order By: Relevance
“…NER and recombinational repair, including XPC recruitment), leading to slower crosslink removal and increased sensitivity to trioxsalen ϩ UVA. This model is broadly consistent with the model of Patrick and colleagues, who based on a series of biochemical and cell biology experiments proposed that, upon cytosine deamination near a cisplatin interstrand crosslink, a uracil-directed BER response will hamper the normal cellular repair processes for the crosslink damage (13). Our studies indicate an interfering role for the NEIL1 glycosylase in the repair of psoralen-induced DNA interstrand crosslinks that involves binding at the crosslink site, seemingly without the formation of a cognate substrate.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…NER and recombinational repair, including XPC recruitment), leading to slower crosslink removal and increased sensitivity to trioxsalen ϩ UVA. This model is broadly consistent with the model of Patrick and colleagues, who based on a series of biochemical and cell biology experiments proposed that, upon cytosine deamination near a cisplatin interstrand crosslink, a uracil-directed BER response will hamper the normal cellular repair processes for the crosslink damage (13). Our studies indicate an interfering role for the NEIL1 glycosylase in the repair of psoralen-induced DNA interstrand crosslinks that involves binding at the crosslink site, seemingly without the formation of a cognate substrate.…”
Section: Discussionsupporting
confidence: 72%
“…Unlike the above work, which suggested a role for BER components in the repair of crosslink adducts, Patrick and co-workers found that cells deficient in BER display a cisplatin-resistant phenotype, which is accompanied by enhanced excision of cisplatin-induced interstrand crosslinks (13). In particular, they demonstrated that the region around a cisplatin interstrand crosslink is susceptible to increased spontaneous decay, namely cytosine deamination, due to a local structural distortion in the duplex.…”
mentioning
confidence: 97%
“…In one study, patients with low human apurinic/apyrimidinic endonuclease (APE1) expression levels had a greater response to cisplatin and a significantly improved survival rate compared to those with high levels of expression [38,39]. In contrast, a recent study by Kothandapani et al observed an increase in resistance to cisplatin in DNA polymerase b (Pol-b)-deficient mouse embryonic fibroblasts following inhibition of APE-1using the small molecule inhibitor, methoxyamine, indicating that a functional BER pathway promotes cell death in response to this platinum drug [40]. This increased resistance was associated with an increased repair rate of inter-strand cross-links and double strand breaks, but not with intra-strand cross-links.…”
Section: Base Excision Repair (Ber)mentioning
confidence: 82%
“…To this end, we determined binary (pol/DNA) and ternary (pol/DNA/dNTP) X-ray crystal structures of human DNA polymerase β (pol β) with 5ClC in the templating position of a 1-nt-gapped DNA duplex (Table 2). Pol β is a model mammalian DNA polymerase involved in base excision repair and may encounter DNA lesions in the templating strand during repair of the genome (32)(33)(34). The binary DNA complex structure with 5ClC in the templating position diffracted to 2.0 Å.…”
Section: Results 5clc Is a Mutagenic Base That Is Easily Bypassed By mentioning
confidence: 99%